Impact of Coaches’ Positive Behavior with Moderation of Players’ Emotions on Psychological Empowerment and Players’ Performance - Dr Mohammed A. Al Doghan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to investigate the effect of coaches' good behavior on players' psychological empowerment and performance in Saudi Arabia. It is seen that the players' performance is affected when they are not correctly cared. The coaches do not train the players with their mindsets and emotions in mind. In domestic-level sports, player performance and psychological empowerment are declining with time. Saudi Arabian football players are surveyed using a Likert scale to acquire the data for this study. A partial least square–structural equation model is employed for data analysis. The study indicated that the influence of coaches' good behavior on psychological empowerment and player performance is substantial. As the newly established links are added to the existing body of literature, the model generated by the current research is novel and a significant contribution to the body of knowledge. The study has important implications for the management and coaches of various teams in their efforts to enhance their players' performance and psychological empowerment. Moreover, the future paths of the present study are outstanding for scholars who wish to extend the model of player performance.